A la recherche du développement socialement durable: concepts fondamentaux et principes de base - Jérôme Ballet; Jean-Luc Dubois; François-Régis Mahieu (Développement Durable et Territoires)
Sustainable development allows the current generation to satisfy its needs without compromising the capacity of future generations to satisfy theirs. This implies that future generations should have in hand at least as many resources, in terms of capital or various potentialities, than the current generation. The social dimension of sustainable development raises the issue of transmitting social assets and potentialities from one generation to the other. These include human capital (education, health), social capital (relationships) as well as any capacity to use in an appropriate way these potentialities. More generally, social sustainability focuses on the conditions for an equitable transmission of capabilities from one generation to the others. It is expected from a socially sustainable development to protect the social potentiality, to improve the person’s capability and to facilitate their transfer from one generation to the next. This implies reviewing the causes that prevent the creation of potentiality (poverty trap), the promotion of capability (social exclusion and vulnerability) and the inter-generational transfer (inequity), in order to define, within the ethical framework of responsibility, a few principles for social precaution, which could be used for the design of public policies.